Exercise intensity at VO2max during cycling: analysis of different criteria in trained individuals - Machado, Carlos Eduardo Polazzo; Caputo, Fabrizio; Denadai, Benedito Sérgio (Brazilian journal of physical education and sport, 2004)
The purpose of this study was to compare values of VO2max (IVO2max) obtained using four different criteria. IVO2max was determined in ten trained male cyclists (VO2max = 64.5 + 5.9 ml.kg-1.min-1) in: 1) Submaximal . incremental exercise (SUB-INC). IVO2max was determined by extrapolation of the submaximal VO2 x workload relationship, using the sub-LT stages from incremental test; 2) Submaximal . constant workload exercise (SUB-CON). IVO2max was determined by extrapolation of the submaximal VO2 x workload relationship, using the final VO2 values during constant workload tests (50 and 70%VO2max); 3) Maximal Power . incremental test (MAX-PMAX): IVO2max was considered as the highest workload sustained during incremental test and; 4) Maximal - VO2max (MAX-VO2max) IVO2max was determined as the lowest workload at which VO2max was attained during the incremental test. No significant differences were found among the IVO2max derived values (W) using the different methods (SUB-INC = 327.3 + 43.6; SUB-CON = 321.9 + 38.5; MAX-PMAX = 349.1 + 34.1; MAX-VO2max = 342.5 + 36.0). However, it was verified a high intraindividual variability in the IVO2max values, mainly between submaximal and maximal criteria. It was concluded that the criteria analyzed in the present study, might determine IVO2max with different physiological meanings. Therefore, the choice of any particular criterion should be done in accordance with the main purpose of the evaluation process (performance prediction, control or prescription of training).